189k views
2 votes
Let f(x) = 2x – 3 and g(x) = 3x – 2. Find the value.

(fog)(-2)
(fog)(-2) =


PLEASE HELP!!!

1 Answer

2 votes

Answer:

Ok:

Explanation:

So f°g . means f(g(x)). (The ° should be more center and bigger but I don't know to do that on a keyboard). f(g(x)) means that you replace the x in f(x) with the g(x) function. i.e:

if f(x) = 2x+2

and g(x) =
x^2

f(g(x)) =
2x^2+2.

Similarly, in this case, we get f(x) = 2x-3 and g(x) = 3x-2.

Then, f(g(x)) or f°g(x) is 2(3x-2) - 3.

And we plug in -2 to solve:

2(3(-2)-2)-3.

and get -19.

Check if I am wrong because everyone makes mistakes but that is the way to solve this.

User TrueinViso
by
7.6k points